Manufacturing and Characterization of Interply Hybrid Polymeric Biocomposite Material Reinforced with Glass and Carbon Fibers. Issue 1 (21st August 2022) - Mihoc, Alexandru Bejinaru; Repanovici, Angela; Drugă, Corneliu; Serban, Ionel; Mit, Leonard
Abstract: The objective of this study is to investigate the mechanical properties of the polymeric composite hybrid type interply reinforced with glass fibers GF and carbon fibers CF with the structure of the material consisting of: a) three layers CF:GF with the sequence [CF/GF/CF]; b) five layers CF:GF with the sequence: 1) [CF/GF/CF/GF/CF] and 2) [CF/CF/GF/CF/CF]. The GF:CF hybrid biocomposite interply type is made using the working methodology based on the Liquid resin Infusion (LRI) and Vacuum infusion techniques. The general mechanical properties are evaluated experimentally using standard tensile and bending tests using five specimens made according to ASTM standards. Based on the experimental results and the diagrams obtained at the tensile and bending tests of the hybrid polymeric biocomposite type interply comparisons are made regarding the mechanical properties of the composite for each type of structure. The general results confirm, from a mechanical point of view, the usefulness of this type of composite for engineering and biomedical applications.